STUDY OF STUDENT SATISFACTION FROM THE MARKETING MIX ASPECT - Ragil Pardiyono (Journal of Business, Management, & Accounting, 2020)
In 2019 Kemenristekdikti [1] had closed 79 PTS, the lack of students was one of the reasons Kemenristekdikti closed private universities (PTS) among a number of other reasons. Higher education is a service industry and service quality is an important determinant of the success of higher education institutions (Landrum et al [2]). Donlagic and Fazlic [3] suggest that service quality is one of the main objectives of the university to attract students and improve institutional processes. In addition, according to Durkin & McKenna [4] universities need to pay attention to marketing principles in order to win the competition, create a brand image and attract prospective students. According to Kotler et al. [5] Instruments that can be used to develop marketing strategies for PTS are 7P marketing mix models with seven dimensions, namely product, price, promotion, place, process, people, physical evidence. Filip [6] recommends that universities use a set of marketing mix variables in designing their marketing strategies. Therefore this study will measure how far the influence of aspects of the marketing mix on student satisfaction. This research was conducted at one private university in the city of Bandung with the number of samples following the Slovin formula. From the results of data processing all the values ??of r-count variable are greater than r-tables. The reliability test results concluded that all research data were feasible to be used to measure the same concept. Based on the data processing, the results show that 73.6% of Student Satisfaction (Y) is influenced by marketing mix variables, namely product (X1), place (X2), price (X3), promotion (X4), people (X5), process (X6), and physical evidence (X7). The partial test results using the t test the result is Y = 0.04 + 0.148X1 + 0.184X2, + 0.098X3 + 0.127X4, + 0.142X5 + 0.171X6 + 0.116X.